Popular series in English language education - Leonhardt, Jan-Erik 1990-; Viebrock, Britta 1973- (narr STUDIENBÜCHER LITERATUR- UND KULTURWISSENSCHAFT, 2025)
English language education that wants to be relevant for today's learners in a media-influenced social environment needs to include series and serials. Our publication enables (future) language teachers to implement series and serials in their English language classrooms purposefully and equip their learners with series_serials literacy, i.e. the ability to deal with series and serials in an autonomous and critical manner. Three introductory chapters provide substantial theoretical and conceptual considerations on serial narratives, objectives and methods of teaching series and serials. Subsequently, experts in the field of language teaching introduce 17 selected series and serials from different genres, ranging from comedies to sci-fi. Each chapter provides in-depth analyses of the chosen example as well as practical teaching suggestions which are accessible online